Camera Archaeologia: A Media Archaeological Investigation into the Contemporary Use of Nineteenth-Century Photographic Processes. - Okudan, Alaz (19: Interdisciplinary Studies in the Long Nineteenth Century, 2025)
As digital technologies determine the practice and experience of everyday life today, the earliest photochemical processes resurface to provide stimulating and provocative modes for visual production. Around the world, a small but attention-worthy number of photographers attempt to rediscover what nineteenth-century photographic processes can offer without turning their backs on digital. From a media archaeological perspective, this article investigates how such a phenomenon challenges linear technological progress narratives by disrupting binary divides between old/new, outdated/contemporary, and analogue/digital. Through interviews with seven Turkey-based photographers who use nineteenth-century photochemical processes, I argue that the contemporary use of the earliest photographic techniques functions as compensation methods for limitations imposed by dominant photographic technologies and culture. By combining alternative forms of photographic expression from the past that are often considered obsolete with digital methods, this article explores 'chemical bending' tactics — technical and temporal hybrids formed to enhance creative freedom and expand the contemporary roles attributed to photography. Contemporary photographers, deeply embedded in digital culture yet drawn to the earliest photochemical techniques, create novel meanings and roles for photographic processes. Ephemeral images become metaphors for life's impermanence; unexpected outcomes express the collaborative creation process with the medium itself; while the material qualities of these practices help restore diminished human sensory experiences in the digital age.